Case Report: Heart aneurysm of unknown origin in a two-year-old child diagnosed in the course of Multisystem Inflammatory Syndrome in Children - Mystkowska, Dominika; Galeczka, Michal; Tarala, Wojciech; Banaszak, Pawel; Sliwka, Joanna; Pawlak, Szymon; Fiszer, Roland (Frontiers in Cardiovascular Medicine, 2024)
We present a case of a 22-month-old boy with a hypokinetic and thin-walled aneurysm of the left ventricle apex. The lesion was diagnosed during routine echocardiography examination in the course of MIS-C, and its occurrence due to MIS-C is plausible. Cardiac magnetic resonance imaging revealed an akinetic aneurysm of the LV apex with a full-wall ischemic scar. Aortography confirmed a normal course of coronary arteries, with adequate perfusion of essential branches and no evidence of stenosis or aneurysms. The boy underwent consultation with the heart team and was deemed eligible for surgery. The aneurysm was excised up to the margin of healthy tissues, and both the surgery and the periprocedural period were uneventful. Determining the origin of the aneurysm is challenging. The most probable etiology appears to be a congenital lesion. Another consideration is an ischemic lesion that may have resulted from impaired coronary circulation during the complicated course of MIS-C. It is possible that this disturbance resolved spontaneously before aortography was performed. Additionally, a complication of pericarditis cannot be entirely ruled out.